Imej karakter animasi Jepun (anime) dalam kalangan remaja di Selangor - Mamat, Roslina; Abdul Rashid, Roswati; Abd Rahim, Normaliza; Abdul Halim, Hazlina (Penerbit Universiti Teknologi Malaysia, 2014)
Japanese animation or anime started to gain interest among teenagers and adults since 1990s. Now the popularity increases parallel with the new technologies. This paper looks into the outcome of conversation among the students at two secondary schools in Selangor, Malaysia. The students were chosen based on the questionnaire. 34 students were selected based on their answers from the questionaire. Based on the interview session, they were fanatic fans of animation and manga. The results of the study revealed that they were five main characteristics in anime characters that the liked; bravery, hardworking, sense of humour, appreciative in relationship as well as individual speciality.